Factors Affecting Employee Performance at the Citra Medika Group Clinic - Crystandy, Muhammad; Sari, Very Novika; Moriza, Tengku (PSPP JOURNALS, 2025)
Employee performance is a key indicator of organizational success, reflecting the ability of individuals or groups to meet established standards, responsibilities, legal norms, and ethical principles. At Citra Medika Clinic, a noticeable decline in employee performance has been observed, raising concerns regarding internal factors affecting productivity. Preliminary assessments suggest that low motivation, poor work discipline, and an unconducive work environment are major contributors to this decline. This study aims to empirically assess the influence of motivation, work discipline, and the work environment on employee performance at Citra Medika Clinic. A quantitative research method with a cross-sectional design was employed. The sample comprised 30 respondents selected from the clinic’s employees. Data were analyzed using univariate, bivariate (chi-square test), and multivariate (logistic regression) statistical techniques at a 95% confidence level (α = 0.05). The findings demonstrate that work motivation (p = 0.007; Exp(β) = 0.567), work environment (p = 0.003; Exp(β) = 0.706), and work discipline (p = 0.001; Exp(β) = 0.325) significantly influence employee performance. Collectively, these factors show a positive and simultaneous effect, with the work environment emerging as the most dominant influence. Based on these findings, it is recommended that management enhance employee motivation and discipline by implementing reward systems and recognizing achievements. Additionally, providing training and professional development aligned with job responsibilities can significantly improve employee competence and performance. These strategies are expected to foster a more productive and sustainable work environment at Citra Medika Clinic.